PENGARUH ANIMASI STORYTELLING TERHADAP PERILAKU PROSOSIAL PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK IKHLAS KOTA PADANG - Reva Aprilia; Indra Yeni; Rakimahwati; Vivi Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of storytelling animation on prosocial behavior in children aged 5-6 years at Taman Kanak-kanak Ikhlas Padang City. This research was motivated by the problem of prosocial behavior in children aged 5-6 years that had not developed optimally. Based on initial observations, 13 out of 20 children were unable to share voluntarily, 14 out of 20 children could not respond spontaneously when their friends were in difficulty, and 15 out of 20 children were not actively involved in group activities. This research employed a quantitative approach with a quasi-experimental method (nonequivalent control group design). The sample consisted of Class B1 as the experimental group and Class B2 as the control group, each comprising 10 children. Data were collected using an observation instrument with 6 statement items covering aspects of sharing, helping, and cooperating, then analyzed through normality testing (Shapiro-Wilk), homogeneity testing (Levene), and hypothesis testing (Independent Samples Test) using SPSS version 27. The results showed that the mean score of the experimental group increased from 9.8 on the pre-test to 20.1 on the post-test with a gain score of 10.3, while the control group increased from 9.4 to 13.5 with a gain score of 4.1. The hypothesis test showed a significance value (2-tailed) of 0.000 < 0.05, meaning the alternative hypothesis (Ha) was accepted. It is concluded that storytelling animation has a significant effect on the prosocial behavior of children aged 5-6 years at Taman Kanak-kanak Ikhlas Padang City.